MODEL INTEGRASI PETERNAKAN SAPI DI DESA WARU BARAT DALAM KONSEP SISTEM PERTANIAN TERPADU - Rahwi Salma Gusti; Amanatuz Zuhriyah; Aminah Happy Moninthofa Ariyani; Elys Fauziyah (Journal of Integrated Agribusiness, 2022)
Madura cattle are a type of local Madura cattle based on the Decree of the Minister of Agriculture which is used as a form of germplasm conservation. Besides playing a role in contributing to the beef cattle population in Indonesia, Madura cattle can also play a role as a source of economic, social, and cultural resources for the people of West Waru Village. Madura cattle management is done traditionally by utilizing the resources in the village but has not been implemented optimally. The purpose of this study was to determine the profile, input, and output of Madura cattle farms in Waru Barat Village, as well as to create an integration model that occurs between the components of Madura cattle and other potential components. This study uses a descriptive qualitative method with the Miles and Huberman model to describe the profile, input, and output of Madura cattle farms. The results showed: (1) the profile of Madura Cattle farms dominated by cattlemen with an age range of 30 to 64 years, with elementary school education, experience in raising livestock for 10 to 30 years, main occupation as a farmer, livestock business orientation as savings, has 1 to 2 cattle, and intensive maintenance; (2) inputs from Madura cattle include feed, drink, medicines, and labor; (3) the output of Madura cattle is manure; and (4) the integration model includes 3 main components, namely the human component, the plant component, and the cattle component.